Pendekatan Psikologi Sosial Budaya dalam Memahami Proses Islamisasi di Tanah Jawa (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
The spread of Islam in Java represents a crucial phase in the historical development of Islam in Indonesia, which occurred peacefully and gradually. This study employs a qualitative approach through literature review, aiming to analyze this dynamic through a socio cultural psychological lens. It explores how Islamic values were accepted, adapted, and internalized by the Javanese society, which already possessed a strong social and cultural system.The research is designed to evaluate the interaction between individuals and groups within the socio cultural context, and to examine how social and cultural developments influenced the community’s openness to Islamic teachings. Key figures in the spread of Islam in Java, such as the Wali Songo and scholars from the Middle East, applied intelligent and contextualized da'wah (Islamic propagation) strategies by integrating Islamic values into local cultural elements such as art, language, and traditions.The findings reveal that the success of Islamization in Java was greatly influenced by Islam’s ability to harmoniously acculturate with local culture, as well as through psychological mechanisms such as social identification, collective acceptance, and reinterpretation of religious values. Therefore, the socio cultural psychological approach provides significant insight into understanding the unique and contextual characteristics of Islam’s spread in Java.